Toward a blue economy : a promise for sustainable growth in the Caribbean - special edition overview 38th Meeting of CARICOM Heads of Government [Conference] - Patil, P.G. (World Bank Group Washington, D.C.US, 2016)
Takes a look at the global oceans and in particular at the Caribbean Sea and its transformation toward a blue economy.